1982
DOI: 10.1677/joe.0.0940011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca2+ deprivation on release of luteinizing hormone induced by luteinizing hormone releasing hormone from female rat pituitary glands in vitro

Abstract: Continuous exposure of hemi-pituitary glands from intact female rats to LH releasing hormone (LH-RH) in vitro displayed three phases in the pattern of LH release: during the first hour release of LH was low (first phase response), then it increased to a higher level during the second hour and remained constant during the next 2 h (second phase response), after which there was a refractoriness of LH release (third phase response). The initial phase response of pituitary glands from intact rats was blocked by EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Recently, de Koning, Tijssen, van Dieten & van Rees (1982) showed that the chelation of Ca2 + by the addition of EGTA resulted in a markedly depressed response of LH release from female rat pituitary glands in response to LHRH.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, de Koning, Tijssen, van Dieten & van Rees (1982) showed that the chelation of Ca2 + by the addition of EGTA resulted in a markedly depressed response of LH release from female rat pituitary glands in response to LHRH.…”
Section: Discussionmentioning
confidence: 99%
“…The following agents were dissolved in the media at final concentrations of 1 to 10 mM: 8-bromoadenosine-3':5'-mono-phosphoric acid (BrcAMP; Boeh¬ ringer), N6 -2' -0 -dibutyryl -adenosine -3',5'-monophos¬ phate (dbcAMP; Boehringer), l-methyl-3-isobutyl-xanthine (MIX; Sigma), NaF (Merck) and theophylline (DBH Chemicals Ltd.). The LH and FSH contents of the media and of saline-extracted pituitary glands were esti¬ mated by radioimmunoassay (Welschen et al 1975;De Koning et al 1982;Jenner et al 1982). Since in one case (10 mM NaF treatment) pituitary wet weight was signifi¬ cantly higher, the results are expressed as µg LH-RP-1 or pg FSH-RP-1/pituitary tissue (mean ± SEM; = 4) instead of per mg pituitary wet weight (see e.g.…”
mentioning
confidence: 99%
“…Many reports deal with a possible role for cyclic AMP as an intracellular mediator for LRH-induced LH release, but only few of them also include FSH release (for review see Tixier-Vidal & Gourdji 1981;De Koning et al 1981). Furthermore, secre¬ tion of FSH apparently is more complex than that (Welschen et al 1975;De Koning et al 1982;Jenner et al 1982). Since in one case (10 mM NaF treatment) pituitary wet weight was signifi¬ cantly higher, the results are expressed as µg LH-RP-1 or pg FSH-RP-1/pituitary tissue (mean ± SEM; = 4) instead of per mg pituitary wet weight (see e.g.…”
mentioning
confidence: 99%